KESENIAN SILAT PANGEAN DALAM MENGURANGI KRIMINALITAS DI KUANTAN SINGINGI: PENDEKATAN BUDAYA DAN PENDIDIKAN KARAKTER - Fadhilah Nursyaviqa Putri; Arifuddin Uksan; Eko G. Samudro (Universitas 17 Agustus 1945 Semarang, 2025)
This study examines the role of the martial art Silat Pangean in Kuantan Singingi Regency, Riau, in reducing crime rates in Singingi Subdistrict. Silat Pangean serves not only as a local cultural heritage but also plays a crucial role in shaping character and moral values within the community. By focusing on the values embedded in the teachings of Silat Pangean, this martial art becomes a constructive medium for enhancing social cohesion and the safety of practitioners, the community, and the broader society from criminal threats. The research method used is descriptive qualitative, applying security theory and cultural communication analysis to explain the impact of this cultural practice on daily life and community security. The research findings indicate that the practice of Silat Pangean contributes to strengthening the social, educational, cultural, economic, and health foundations in Kuantan Singingi Regency and helps in reducing crime rates.